A Black Mirror of Bright Ideas: Could Media Educate towards Positive Creativity? - Simon Majed Ceh; Izabela Lebuda (MDPI AG, 2022)
With the media's omnipresence, beneficial and detrimental effects on human behavior-including creativity-are being widely discussed. This essay presents potential benefits of passive and active media use for enhancing creative thinking and behavior. Based on the classic socio-cognitive theory of observational learning and stressing the importance of creative self-beliefs, certain types of media content and activities are highlighted to demonstrate how traditional and modern media can shape positive creativity-contributing to novel and valuable behavior from both individual and social points of view. The discussion proceeds to link media influence with creative skills, creative self-beliefs, and group creativity, emphasizing the necessity of media education and systematic scientific research on the topic.